2013
DOI: 10.2174/1381612811319350005
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Mesoporous Materials as Excipients for Innovative Drug Delivery and Formulation

Abstract: Due to uniquely ordered nanoporous structure and high surface area as well as large pore volume, mesoporous materials have exhibited excellent performance in both controlled drug delivery with sustained release profiles and formulation of poorly aqueoussoluble drugs with enhanced bioavailability. Compared with other bulk excipients, mesoporous materials could achieve a higher loading of active ingredients and a tunable drug release profile, as the high surface density of surface hydroxyl groups offered versati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 150 publications
0
9
0
Order By: Relevance
“…S5, Supplementary materials). Furthermore, in the later stage, apatite precipitations would also take part in retarding the drug release process (not discussed in detail) [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S5, Supplementary materials). Furthermore, in the later stage, apatite precipitations would also take part in retarding the drug release process (not discussed in detail) [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, pure PLGA or other degradable and biocompatible polymer implants embedded into the bone defect caves would induce the significant decrease of pH values by the acidic degradation products [15,16] bacillus [17]. Alternatively, mesoporous silica-based materials [18][19][20][21], may provide a more advantageous choice for controlled and localized ATD delivery without causing significant pH value decreases, owing to the extensive nanoporous structure.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement of osseointegration to shorten the healing period has been the main focus for implant surface modifications. [1][2][3][4][5] It has been suggested that surface roughness modifications on the micrometer level is one of the important factors for successful osseintegration of implants. 6,7 The socalled moderately rough surface has been reported to present the strongest bone response.…”
Section: Introductionmentioning
confidence: 99%
“…The need of immobilizing the complex is due to the fact that mesoporous silica has the ability to protect the drug (the metallic complex), from decomposition. The silica materials have the ability to seal the drug in order to prevent the drug from being released prior to reaching the target‐site by modified pore openings with caps, and protect the body from possible side‐effects of the drug . Although the effect on urease activity decreases, once the complex is immobilized, its secondary effects after administration might be reduced, further studies being necessary in order to analyses the toxicity of both complex and silica materials for viable cells, as well as for the drug release control.…”
Section: Resultsmentioning
confidence: 99%